Evaluation of a partial ban of Rx-rebates in Germany using difference-in-differences - Maximilian M. Gail; Georg Goetz; Daniel Herold; Jan Schäfer (Philipps-University Marburg, School of Business and Economics, 2025)
In December 2020, Germany implemented a policy restricting online pharmacies from offering rebates on prescription drugs to members of the statutory health insurance. This policy change created a natural experiment, allowing us to analyze its impact on the pharmaceutical market using Difference-in-Differences. Utilizing a novel dataset, we find that the ban led to a shift in consumer behavior, increasing offline pharmacy Rx sales by 1.36 % to 1.65 %. However, the policy's effects were unevenly distributed across pharmacies. While all pharmacies experienced some benefit, the impact was disproportionately larger for higher-revenue pharmacies. For instance, pharmacies in the lowest revenue decile saw a modest annual profit increase of e 1,360, whereas those in the highest decile gained more than five times that amount. Our findings indicate that the introduction of VOASG alone was insufficient to reverse the declining trend in pharmacy numbers in Germany. To strengthen the comprehensive supply of pharmaceuticals to the general population, additional reforms are necessary.
Keywords: L5; I18; 330; Pharmacies; Prescription Drugs; Resale Price Maintenance; Regulation; Public Health